THE ROLE OF HUMAN RESOURCES IN CUSTOMER SERVICE QUALITY AT PT. BANK SUMUT MEDAN COORDINATOR BRANCH - Muhammad Dimas Alfahri; Muhammad Gilang Anugrah; Alya Azizah; Dwi Indah Lestari; Melisa Zuriani Hasibuan; Julianto Hutasuhut; Toni Hidayat (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
Human Resource Development is a strategic element for Bank Sumut to realize excellent service and maintain competitive advantage amidst the increasingly tight competition in the banking industry. Through structured and sustainable training and development programs, Bank Sumut equips employees with the knowledge, skills, and attitudes needed to provide the best service to customers. The main focus of human resource development includes improving communication skills, empathy, problem solving, and in-depth understanding of bank products and services. Competent employees are not only able to handle transactions efficiently, but also provide fast and precise solutions to various customer problems . Supervision and evaluation of training programs are carried out continuously to ensure their effectiveness, while awards and incentives are given to high-performing employees to strengthen the organizational culture that supports excellent service. In addition, the role of customer service and product knowledge are important components in providing valid information according to operational standards. By focusing on comprehensive human resource development , Bank Sumut ensures that every interaction with customers reflects a commitment to excellent service. This increases customer satisfaction and loyalty, strengthens the bank's reputation in the eyes of the public, and supports sustainable business growth. Competent, motivated, and customer-oriented human resources are the main key in creating a positive service experience and differentiating Bank Sumut from other financial institutions.